Comparative financial systems - Smith, Paul F. (New York, N.Y. : Praeger, 1982)
This book records an exploration of a massive body of statistical information in a search for clues to the economic role of money and financial systems. It began with the assumption that banks and other financial institutions respond to demand pressures in much the same way in all countries and that the differences that appear in their financial statements should provide evidence of differences either in market pressures or in control techniques.
Includes index.
Bibliography: p. 149-155.
usc 10/04/18
Loans
Keywords: Finance; Financial institutions